THE INFLUENCE OF WORK ENTHUSIASM AND JOB PROMOTION ON JOB SATISFACTION, ITS IMPACT ON EMPLOYEE PERFORMANCE AT THE LHOKSEUMAWE CITY REGIONAL FINANCIAL MANAGEMENT LHOKSEUMAWE AGENCY - Muhammad Fadhil; Marbawi; Ibrahim Qamarius (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of work enthusiasm and job promotion on job satisfaction and its impact on employee performance at the Regional Financial Management Agency of Lhokseumawe City. The dependent variables of this study are work enthusiasm and job promotion. The independent variable is employee performance, and the intervening variable is job satisfaction. The population in this study is 70 employees at the Regional Financial Management Agency of Lhokseumawe City. The sampling technique used a census technique and obtained a sample of 70 employee respondents at the Regional Financial Management Agency of Lhokseumawe City. The research method used was a quantitative method, for the data analysis method using path analysis. The results of this study indicate that work enthusiasm and job promotion have a significant effect on job satisfaction, furthermore, work enthusiasm and job promotion and job satisfaction have a significant effect on employee performance at the Lhokseumawe City Regional Financial Management Agency. In this study, job satisfaction partially mediates the relationship between work enthusiasm and job promotion on employee performance at the Lhokseumawe City Regional Financial Management Agency.